Essential of Graptophyllum pictum for the medical and dental purposes - Dhywinanda, Devin Elysia; Dien, Sinta Nuriyah; Chairuly, Hadfi Dhaky; Sakti, Gilang Ratri; Tandra, Renata Jasmine Ramadhanty Felisha; Kartikasari, Nadia; Mundiratri, Karina; Sitalaksmi, Ratri Maya; Aljunaid, Mohammed Ahmed Qasim Saleh (Faculty of Dental Medicine Universitas Airlangga, 2023)
Background: The use of plants for medicinal purposes continues to expand rapidly across the world. Up to 80% of the world's population is estimated to rely heavily on herbal medicines for their primary health care. Graptophyllum pictum leaves (GPL) have long been used as herbal medicine for several diseases or health conditions. However, until now, there have been only limited studies regarding laboratory experiments and the pharmacological effects of GPL. Purpose: To summarize the phytopharmacology aspect of GPL used for medical and dental purposes. Review(s): Based on the 36 articles included, GPL is widely used in medicine and dentistry, such as for treatment of hemorrhoids, periodontitis, and candidiasis, due to its anti-inflammatory, antioxidant, and antifungal properties. However, the current research study designs are still in vitro and in vivo experiments. Continuing experiments and clinical tests are needed to explore the essential use of the GPL. Conclusion: GPL can be used for medical and dental purposes due to its anti-inflammatory, antioxidant, antibacterial, and antifungal properties.